Human and Canine Blastomycosis: A Common Source Infection - Matthew W Morgan; Irving E Salit (Canadian Journal of Infectious Diseases)
In fall 1993 a man and a dog developed blastomycosis after visiting an island off Bayfield Inlet, Georgian Bay, located near Parry Sound, Ontario. The man recovered but the dog died of blastomycosis. It was hypothesized that the common source of exposure was the island since the permanent residences of the two cases were in different cities. One further case of human infection, based on positive serology, and four additional cases of probable canine blastomycosis were identified. All cases had travelled to Bayfield Inlet during summer and early fall 1993. To the authors’ knowledge this is the first Canadian report of a common source of infection of human and canine blastomycosis. This report also provides evidence for a new endemic area of blastomycosis infection.